Miniature za klavir Primoža Ramovša - Loparnik, Borut (Muzikološki zbornik, 2007)
Primož Ramovš (1921-1999) wrote his piano Miniature (Miniatures) during the autumn of 1945. After finishing his studies with Slavko Osterc in Ljubljana (1941) and taking advanced courses with Alfredo Casella in Rome (1941-1943), these pieces were his second major works. He conceived them as variations on the chorale that introduced the final movement of his Second Symphony (1943-1944). At first, he wanted to name them variations without a theme. Throughout the ten parts, the introductory musical thought unfolds in the formof two contrasting themes, both included either successively or singly; in the original melodic diction they appear augmented only in the middle section of the final part. Thus the piece is not, in fact, a set of variations without a theme, but rather has a "concealed" theme. Due to (possibly various) external circumstances the composer eventually entitled them, perhaps not the most conveniently: Miniature (Miniatures). They were published in 1955 but were not performed as a whole until the autumn of 1963, and even then only were only performed within the context of a broadcast programme. The cycle represents the beginnings of Ramovš's autonomous artistic path. Various idioms of "common" neoclassicism from the period betweenthe wars are intertwined with other modernist principles introduced by Osterc, along with the older compositional repertoire that Ramovš was familiar with from concerts and his piano studies. Both bear witness to the features of neoclassicism in Slovenia before 1945, but above all reveal a composer with distinctive innovative courage and an "improvisational" imagination, liberal in design and oriented towards extreme regions of (piano) sonorities.
Keywords: 20.st.; glasba; music; neoklasicizem; Osterc, Slavko, 1895-1941; Ramovš, Primož, 1921-1999; Ramovš, Primož: Miniature za klavir; Slovenia; Slovenija